Art and culture week at IFSC Araranguá: dialogue circle and video poems in favor of anti-racist education (Citizenship in Action: Extension and Culture Magazine, 2023)
This article presents two extension activities, a dialogue circle and video poems, on the topic of racism. Such activities were part of the VI Week of Art and Culture at IFSC Araranguá. The general objective was to promote reflections on racism, encouraging anti-racist education through the reading and discussion of works by black authors. The contents of the conversation circle and the video poems were presented by high school students, possibly allowing the classroom reflections to reach a wideraudience, such as the institution's servers, other students, family members and the external community of IFSC Araranguá. It was observed that the activities provided moments of reflection among its participants, according to the qualitative data collection through a questionnaire with open and closed questions. Such activities foster the need for dialogue and reflection as anti-racist actions in education.
Keywords: anti-racism; art; culture; education